A Generalization of Caristi's Fixed Point Theorem in the Variable Exponent Weighted Formal Power Series Space. (7th June 2021) - Bakery, Awad A.; El Dewaik, M. H.
Abstract : Suppose p n be sequence of positive reals. By H w p n, we represent the space of all formal power series ∑ n = 0 ∞ a n z n equipped with ∑ n = 0 ∞ λ a n / n + 1 p n < ∞, for some λ > 0 . Various topological and geometric behavior of H w p n and the prequasi ideal constructs by s -numbers and H w p n have been considered. The upper bounds for s -numbers of infinite series of the weighted n -th power forward shift operator on H w p n with applications to some entire functions are granted. Moreover, we investigate an extrapolation of Caristi's fixed point theorem in H w p n .